PENGARUH COVID 19, BERITA PANDEMI DAN BITCOIN DAN EMAS TERHADAP PEREKONOMIAN DI INDONESIA - Suyono Suyono (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2022)
The Covid-19 pandemic is a serious threat to the world's economy, including Indonesia. This study aims to determine: 1. Will Covid-19 worsen/increase economic growth in Indonesia. 2. Whether the ongoing pandemic news will worsen economic growth in Indonesia and 3. Can both bitcoin and gold commodities improve/worsen the economy in Indonesia. The method used in this research is descriptive qualitative method, which is more specifically, using interactive data analysis method (Miles and Huberman 1992:20 model). Which consists of 4 stages as follows: 1. Data collection, 2. Data presentation, 3. Data reduction and 4. Conclusion. Data collection techniques were carried out using literature studies derived from scientific articles that were relevant to the research problem/title from articles indexed by Scopus. The data analysis technique uses interactive data analysis/descriptive analysis from previous research and phenomena during the pandemic, namely March 2020 s.d. July 2021, using Milles and Huberman model analysis. The results of this study are: 1. The occurrence of the Covid 19 outbreak, pandemic news has a negative effect on economic growth in the world, including in Indonesia. While bitcoin and gold can have a positive effect on economic growth in Indonesia. The conclusion is that the corona virus 19, pandemic news has a negative impact on economic growth in Indonesia, while bitcoin and gold have a positive effect on economic growth in Indonesia. Suggestions to the government, in order to quickly recover the economy, the government accelerates the booster vaccine for its people, while the advice for the public is to quickly follow the booster vaccine, and always obey health protocols so that the economy in Indonesia can recover quickly. As for bitcoin and gold, they can have a positive effect on the economy during a pandemic, so the government needs to promote and promote it.